2011
DOI: 10.1002/gcc.20890
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic disparity between primary and metastatic melanoma in human patients

Abstract: It is commonly accepted that cancer cell progression is accompanied by accumulation of genetic changes. Here we searched for copy number variations in melanoma and asked whether homozygous losses always cumulate during tumor cell progression. Therefore we investigated either melanoma cell lines or tissue derived from the primary lesion and from the lymph node metastasis of the same individual patient. In vitro studies of melanoma cell lines revealed high migratory and anchorage independent growth of metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Metastatic melanoma from spleen (Mel.7), skin (Mel.17), lymph node (Mel.15) and ovary (Mel.14) were isolated and cultivated as described previously 28. IGR37 and IGR39 were kindly provided by Dr. Peter Petzelbauer (Department of Dermatology, Vienna) and cultivated as described previously 29. HeLa cells and melanocytes were obtained from ATCC, and human adult low calcium high temperature keratinocytes (HaCaT) cells were obtained from DKFZ (Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Metastatic melanoma from spleen (Mel.7), skin (Mel.17), lymph node (Mel.15) and ovary (Mel.14) were isolated and cultivated as described previously 28. IGR37 and IGR39 were kindly provided by Dr. Peter Petzelbauer (Department of Dermatology, Vienna) and cultivated as described previously 29. HeLa cells and melanocytes were obtained from ATCC, and human adult low calcium high temperature keratinocytes (HaCaT) cells were obtained from DKFZ (Germany).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the main cause of intertumor (intrapatient) heterogeneity ( Figure 1 B ) is intratumor heterogeneity ( Figure 1 A ) of the primary tumor [102] , [183] , [184] . To be precise, heterogeneity of circulating tumor cells (CTCs) or CTC clusters.…”
Section: Intertumor Heterogeneity In Melanomamentioning
confidence: 99%
“…Moreover, they examined 10 corresponding primary tumors and found that 5 (50%) patients exhibited additional LOH in metastases. Furthermore, Swoboda et al [184] found deletions exclusively in the primary melanoma cell line or in the matched metastatic melanoma cell line.…”
Section: Intertumor Heterogeneity In Melanomamentioning
confidence: 99%
“…Several studies have reported alterations in gene expression and phenotypic heterogeneity between metastatic and primary cancer sites [ 21 ]. The heterogeneity is primarily caused by differences in gene expression at different metastatic sites.…”
Section: Alternative Therapeutic Approachesmentioning
confidence: 99%